2012
DOI: 10.1097/fch.0b013e31826665d0
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of Grandparent Caregiving and Life Satisfaction Among Rural Chinese Older Adults

Abstract: This study examined how life satisfaction and grandparent caregiving intensity changed over time among rural Chinese older adults, and whether there was a leading predictor between grandparent caregiving intensity and life satisfaction. Using 4 waves of data from the Well-being of Elderly in Anhui Province of China (N = 1704), we applied latent difference score analysis to explore this relationship. Results indicated that grandparent caregiving intensity decreased and life satisfaction increased over time. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 9 publications
0
26
2
1
Order By: Relevance
“…Generational differences in beliefs and practices of raising children are also common in immigrant families, which may result in conflict and disagreement across generations. In sum, although numerous studies have reported the psychological benefits of providing child-care support to children among urban and rural Chinese older adults (Chen and Liu 2012; Xu et al 2012), our study failed to find such benefits for parent–child relationships among older Chinese immigrants.…”
Section: Discussioncontrasting
confidence: 93%
“…Generational differences in beliefs and practices of raising children are also common in immigrant families, which may result in conflict and disagreement across generations. In sum, although numerous studies have reported the psychological benefits of providing child-care support to children among urban and rural Chinese older adults (Chen and Liu 2012; Xu et al 2012), our study failed to find such benefits for parent–child relationships among older Chinese immigrants.…”
Section: Discussioncontrasting
confidence: 93%
“…The current study also revealed that providing support to others was positively associated with optimal life satisfaction by alleviating the sense of loneliness, which echoes other scholars who have argued that achieving an altruistic goal is salient to promoting life satisfaction for older adults and that providing support to adult children or grandchildren could improve life satisfaction of older adults. 21 , 54 Therefore, we suggest that awareness of the benefits of reciprocal support (ie, giving and receiving) for solitary older adults should be improved. We should remove the stereotype that the majority of older adults are frail and dependent on help from others.…”
Section: Discussionmentioning
confidence: 99%
“…11 , 18 , 19 Recent studies have found that both receiving support from and providing support to adult children or grandchildren can improve the family status of older adults, increase their self-esteem and feelings of commitment to others, and enhance their life satisfaction. 20 , 21 In addition, the size of older adults’ social networks, their frequency of contact with relatives and friends, and the support received from children have all been found to be negatively associated with the sense of loneliness, possibly because sense of loneliness usually stems from feelings of being isolated from significant relationships and being rejected by others. 18 , 22 Sense of loneliness, which is characterized by feelings of depression and anxious response to social isolation, 23 is a distressing problem faced by many older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that psychological well‐being is associated with depressive symptoms, several previous studies were inconsistent with our findings. One study argued that as the intensity of grandparenting increased, well‐being decreased (Xu et al ., ). Another previous study argued that full‐time caregiving among grandmothers was associated with lower life satisfaction than was part‐time caregiving (Bowers and Myers, ).…”
Section: Discussionmentioning
confidence: 97%